Identification of ferroptosis-associated genes exhibiting altered expression in pulmonary arterial hypertension - Fan Zhang (AIMS Press, 2021)
Pulmonary arterial hypertension (PAH) is a life-threatening illness and ferroptosis is an iron-dependent form of regulated cell death, driven by the accumulation of lipid peroxides to levels that are sufficient to trigger cell death. However, only few studies have examined PAH-associated ferroptosis. In the present study, lung samples mRNA expression profiles (derived from 15 patients with PAH and 11 normal controls) were downloaded from a public database, and 514 differentially expressed genes (DEGs) were identified using the Wilcoxon rank-sum test and weighted gene correlation network analyses. These DEGs were screened for ferroptosis-associated genes using the FerrDb database: eight ferroptosis-associated genes were identified. Finally, the construction of gene-microRNA (miRNA) and gene-transcription factor (TF) networks, in conjunction with gene ontology and biological pathway enrichment analysis, were used to inform hypotheses regarding the molecular mechanisms underlying PAH-associated ferroptosis. Ferroptosis-associated genes were largely involved in oxidative stress responses and could be regulated by several identified miRNAs and TFs. This suggests the existence of modulatable pathways that are potentially involved in PAH-associated ferroptosis. Our findings provide novel directions for targeted therapy of PAH in regard to ferroptosis. These findings may ultimately help improve the therapeutic outcomes of PAH.